Answer: a = 11.1
Explanation:
a(0.3 - y) + 1.1 + 2.4x = 0
Let y = 1.3 → a(0.3 - 1.3) + 1.1 + 2.4x = 0 → -a + 1.1 + 2.4x = 0 → a = 1.1 + 2.4x
(y - 1.2) = -1.2(x - 0.5)
Let y = 1.3 → (1.3 - 1.2) = -1.2(x - 0.5) → 0.1 = -1.2x + 0.6 → -0.5 = -1.2x →
![(50)/(12)=x\ \rightarrow\ (25)/(6)=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bpktps1ny9v14f05vvtxdm6d4br1u3qkk1.png)
a = 1.1 + 2.4x
![=1.1+2.4\bigg((25)/(6)\bigg)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l50zn2gv7nst7hlrdf3ckym9dy4cq1u80g.png)
= 1.1 + 0.4(25)
= 1.1 + 10
= 11.1